Commonwealth of Massachusetts. By the governor, a proclamation, for a day of public thanksgiving : ... Thursday the fifteenth day of December next ... Given at the Council-chamber, in Boston, this sixth day of October ... one thousand seven hundred and ninety-six . (Young & Minns, State printers, 1796)
October 6, 1796 Proclamation by Governor Samuel Adams setting December 15th as a day of thanksgiving for free elections, harvest, health, and other blessings.